Pengendalian cacat tuang produk cor aluminium ADC 12 gravity-die-casting: Studi kasus di PT Sinar Mulia Teknalum - Setyo, Noor; Hayati, Nur (Badan Kerja Sama Teknik Mesin Indonesia, 2024)
Casting defects in cast products will always appear due to the unexpected presence of the X Factor in every casting process. Casting experts can only minimize the appearance of casting defects by carrying out controls starting from the product design process, process design, pattern, mold, melting, and casting to obtain cast products that have quality standards that are free from casting defects. This case study aims to determine the quality control methods carried out by the metal casting industry PT Sinar Mulia Teknalum in overcoming casting defects in ADC 12 Gravity-Die-Casting aluminium alloy cast products, namely adapters, knobs, break drums, and cigarette rolling bases which have shrinkage defects, porosity, mis-run, porous and other types of defects. Quality control for casting defects is carried out in four stages continuously using a solution method that is also a problem solver to Plan, Do, Check, and Action (PDCA) quality control and supporting Seven Tools as a quality control tool. The process of observing casting defects is carried out visually (sight), based on initial data before control is carried out, the product has casting defects of 51.16% shrinkage, 27.91% porosity, 11.63% mis-run, 6.98% porousness, and other defects below 2.33%. Casting defects occur due to the influence of human factors, tools, materials, methods, and environment. After recommendations from the quality control team, corrective steps are taken for each cause of casting defects. Overall casting defects experienced a total interconnected decrease of 29.07%, which included 9.30% shrinkage, 6.98% porosity, 6.98% mis-run, 4.65% porousness, and other defects as much as 1.16%. This reduction in casting defects can be seen as a guide or reference for the work of the PDCA cycle in overcoming casting defects on an ongoing basis in the future.